2002
DOI: 10.1002/bip.10081
|View full text |Cite
|
Sign up to set email alerts
|

Binding modes of cyclic AMP and environments of tryptophan residues in 1:1 and 1:2 complexes of cyclic AMP receptor protein and cyclic AMP

Abstract: Cyclic AMP (cAMP) receptor protein (CRP) forms 1:1 and 1:2 complexes with cAMP, and the former complex is considered to be the most active form of CRP in binding to specific DNA sequences and in modulating gene transcription by RNA polymerases. We examine the cAMP binding modes and structural changes of CRP upon cAMP binding by UV resonance Raman spectroscopy. The Raman spectra of CRP-(cAMP)(1) and CRP-(cAMP)(2) extracted from those of CRP-cAMP mixtures at varied mixing ratios clearly show that the hydrogen bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…50 Additionally, the 1360 cm −1 is not always discernible in non-resonance spectra, 51 even if readily apparent in the resonance Raman spectra. 48,49 …”
Section: Resultsmentioning
confidence: 99%
“…50 Additionally, the 1360 cm −1 is not always discernible in non-resonance spectra, 51 even if readily apparent in the resonance Raman spectra. 48,49 …”
Section: Resultsmentioning
confidence: 99%
“…Crystallographic studies of E . coli CRP have been performed to determine the structure of a CRP-cAMP complex, its target DNA, and the carboxyl-terminal domain of the RNA polymerase (RNAP) α-subunit[ 15 19 ]. It is shown that CRP contains a helix-turn-helix DNA-binding motif in its carboxyl-terminal domain and a cAMP-binding site in its amino-terminal domain[ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The downshifted W6 band serves as a marker of N 1 ‐deuteration in visible Raman spectra 5, 23. In UV resonance Raman spectra excited at 229 nm, the W4 band can be detected but the W6 band is not clear 27, 38, 39. The wavenumbers of the Wd4 (≈1445 cm −1 ) and Wd5 (≈1405 cm −1 ) bands of Trp‐ d 5 also depend on hydrogen bonding in a way similar to that of the W4 and W6 bands of Trp 8.…”
Section: Resultsmentioning
confidence: 99%